Management of Maritime Education in Practical Learning on Training Ships: Case Study of Cadets in Navigation Practice - Arleiny Arleiny; Iie Suwondo; Samsul Huda; Retno Sawitri Wulandari; Mukhammad Jamaludin (Journal of Innovation in Educational and Cultural Research, 2025)
Maritime education management plays a crucial role in ensuring cadets are well-prepared for the maritime industry through practical learning onboard training ships. This study focuses on how practical learning on training ships, such as KL Husni Thamrin, KL Bung Tomo, KL Malahayati, KL Laksamana Muda John Lie, KL Sultan Hasanudin, KL Frans Kaisepo, KL Barombong bridges the gap between theoretical knowledge and real-world experience. Cadets are provided with hands-on experience in navigation, ship handling, and emergency simulations, following international standards set by the International Maritime Organization (IMO). This practical approach helps develop essential technical and non-technical competencies required in the maritime industry. However, challenges such as resource limitations, weather conditions, and high operational costs require efficient management and innovative teaching strategies. This article explores these aspects and offers recommendations to enhance the effectiveness of maritime education management for cadets' onboard learning experiences. Ultimately, this study emphasizes the need for continuous improvement in educational management frameworks within maritime institutions, suggesting that collaborative efforts with industry stakeholders and the adoption of innovative teaching methods can further enhance the training quality for future maritime professionals. By addressing these challenges and leveraging technological advancements, maritime education can ensure its graduates are not only competent but also adaptable to the ever-evolving demands of the global maritime landscape.